Bridging the Gap Between Policy and Practice: A Critical Discourse Analysis of Local Wisdom Integration in Pasuruan City's Urban Planning Regulations - Tristan Rokhmawan; Sainee Tamphu (Anglophile Journal, 2024)
The Pasuruan City Government, rich in historical and cultural heritage, aims to integrate local wisdom into spatial planning through Regional Regulation Number 4 of 2021 (Rencana Pembangunan Jangka Menengah Daerah or RPJMD 2021-2026) and Regional Regulation Number 1 of 2022 (Rencana Tata Ruang Wilayah or RTRW 2021-2041). However, these policies often prioritize colonial heritage over local traditional culture. This study uses Critical Discourse Analysis (CDA) to examine the formulation, implementation, and community impact of these policies. CDA reveals the power dynamics, ideologies, and specific interests within policy discourse. The research analyzes the government's policy direction and sensitivity towards local wisdom, focusing on the discourse content and structure in the RPJMD and RTRW documents, as well as their intertextuality. Findings indicate a greater emphasis on preserving colonial-era buildings rather than local traditional culture. Recommendations include developing inclusive policies that balance physical infrastructure development with the preservation and promotion of local culture.